Pravljice na Glasbeni šoli Jesenice - Jamar, Nina (Šolska knjižnica, 2020)
The article describes how fairy tales are used in the Music School Jesenice library to present the library to the students and introduce the instruments taught at the Music School Jesenice to preschool children from the Jesenice Kindergarten. The youngest children attending the Music School Jesenice started visiting the school library in the school year 2006/2007. From 2009 onwards, the children from the Jesenice Kindergarten were also invited to visit the Music School Jesenice. The topic of fairy tales used with the youngest children attending Music School Jesenice and preschool children from the Jesenice Kindergarten was mostly related to music, reading, books or library. From time to time, we also read folk tales. Lately, fairy tales are also narrated with the help of kamishibai.
Keywords: Glasbena šola Jesenice; glasbena vzgoja; glasbene šole; kamišibaj; pravljice; šolske knjižnice; učne metode